Pengaruh Literasi Keuangan, Analisis Fundamental, dan Besar Dividen Terhadap Minat Investasi Saham : (Studi Kasus Pada Investor Bandar Lampung) - Hernes, Yolanda; Indrayenti , Indrayenti (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research has the purpose to prove financial literacy, fundamental analysis, and dividend size have impact on interesto of stock investment in Bandar Lampung investor. Independent variable of this research are financial literacy, fundamental analysis, and dividend size. While, dependent variable of this research is interest in stock investment. Population of this research is Bandar Lampung investor. The sampling technique used was unknown population. Samples taken amounted to 100 people. Data collection method used was questionnaire. Resultan of this research is financial literacy, fundamental analysis, and dividend size proved to have an effect on interest in stock investment